Runx2 Regulates Endochondral Ossification Through Control of Chondrocyte Proliferation and Differentiation. (December 2014) - Chen, Haiyan; Ghori‐Javed, Farah Y; Rashid, Harunur; Adhami, Mitra D; Serra, Rosa; Gutierrez, Soraya E; Javed, Amjad
ABSTRACT Synthesis of cartilage by chondrocytes is an obligatory step for endochondral ossification. Global deletion of the Runx2 gene results in complete failure of the ossification process, but the underlying cellular and molecular mechanisms are not fully known. Here, we elucidated Runx2 regulatory control distinctive to chondrocyte and cartilage tissue by generating Runx2 exon 8 floxed mice. Deletion of Runx2 gene in chondrocytes caused failure of endochondral ossification and lethality at birth. The limbs of Runx2ΔE8/ΔE8 mice were devoid of mature chondrocytes, vasculature, and marrow. We demonstrate that the C‐terminus of Runx2 drives its biological activity. Importantly, nuclear import and DNA binding functions of Runx2 are insufficient for chondrogenesis. Molecular studies revealed that despite normal levels of Sox9 and PTHrP, chondrocyte differentiation and cartilage growth are disrupted in Runx2ΔE8/ΔE8 mice. Loss of Runx2 in chondrocytes also impaired osteoprotegerin‐receptor activator of NF‐κB ligand (OPG‐RANKL) signaling and chondroclast development. Dwarfism observed in Runx2 mutants was associated with the near absence of proliferative zone in the growth plates. Finally, we show Runx2 directly regulates a unique set of cell cycle genes, Gpr132, Sfn, c‐Myb, and Cyclin A1, to control proliferative capacity of chondrocyte. Thus, Runx2 is obligatory for both proliferation and differentiation of chondrocytes. © 2014 American Society for Bone and Mineral Research.